THE ISSUE OF SOCIAL STATUS AND SOCIAL ROLE WITHIN THE SYSTEM OF CHARACTERS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive study of sociolinguistics, its contemporary significance, and the concepts of social status and role within society, illustrating these aspects through the speech of characters in Abdulla Khakhhor’s short stories.
Keywords: story, character, social status, social role, Uzbek literature, individual, society, episode, protagonist, social position.